Oxidative status in nestlings shows different associations with parental carotenoid-based plumage ornaments depending on parental sex and year: a study of rock sparrows Petronia petronia. Issue 6 (2nd November 2017) - Cantarero, Alejandro; López-Arrabé, Jimena; Palma, Antonio; Moreno, Juan
Abstract : Carotenoid-based colouration in birds has been suggested to be a sexually selected signal, allowing individuals to obtain reliable information about the quality of antioxidant resources. Moreover, oxidative stress levels during early development may have medium- and long-term fitness consequences. Rock sparrows ( Petronia petronia ) display a carotenoid-based breast patch in both sexes which has been shown to function as a signal of phenotypic quality in sexual and social interactions. We studied a rock sparrow population in central Spain aiming to test whether the extent of the carotenoid-based breast patch is associated with offspring growth and oxidative status. We have used plasma malondialdehyde (MDA) level in plasma as a measure of oxidative damage, and total antioxidant status of plasma (TAS) and total glutathione (tGSH) levels in red blood cells as measures of antioxidant defences. The study included the extremely late breeding season of 2013 and the phenologically more normal season of 2014. Unfavourable conditions for breeding resulted in smaller nestlings in 2013. Male breast patch size showed a negative association with nestling tarsus length and, strikingly, a positive association with nestling MDA. It also showed a positive relationship with nestling wing length in interaction with year. Nestlings in late and larger broods showed higher tGSH levels. Female breast patch size showed positive associations with nestling tGSH levels, indicating positive links of maternal ornamentation with offspring condition. Moreover, TAS values were only positively associated with female patch size under favourable conditions, as shown by the interaction with year. Associations of carotenoid-based parental plumage ornaments with offspring growth and oxidative status depends on parental sex and environmental conditions. Carotenoid-based plumage traits signal parental quality in female rock sparrows, while paternal ornaments seemingly do not reflect parental quality. To our knowledge, this is the first study to investigate the association between female plumage ornaments and offspring antioxidant capacity. The same signal may reflect different parental attributes in the two sexes in sexually monomorphic species.